The Ideal of Learning Leadership in Primary School - Lailatul Isnaini; Abdi Abdi; Ismail Ismail (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
The study aims to identify the manifestation of learning leadership characteristics in school. It also explores the concept of the leadership as a part of learning process throughout human life and investigate on how learning plays role in leadership. In order to meet the purpose of the research, the qualitative approached was employed, as it is in line with this particular study which is descriptive in nature. In accordance with many of the previous theories regarding the learning leadership, it is found that the application of learning leadership aids the leader of both schools to be a better leader. The improvement and the successful of the program indirectly derived from the manifestation of the characteristics of learning leadership namely faith in oneself, the aspiration towards excellence, the tenacity to challenge themselves, the engagement of support from others, and the continuous deliberate practice.